ANT 2018/19: AWI airborne ultra-wideband radar data over the ice shelves and ice rises in eastern Dronning Maud Land (East Antarctica) - Steven Franke; Daniela Jansen; Reinhard Drews; Daniel Steinhage; Veit Helm; Olaf Eisen (PANGAEA, 2025)
We present a high-resolution airborne radar data set for the Princess Ragnhild Coast, Dronning Maud Land, East Antarctica. The radar data has been acquired in December 2018 and January 2019 with the Alfred Wegener Institute (AWI) multichannel ultra-wideband radar mounted on the Polar6 aircraft. Radar profiles cover the Princess Ragnhild Coast in Dronning Maud Land, East Antarctica (20° E - 28° E). They cover the western Roi Baudouin Ice Shelf, the Jotneisen Ice Shelf, and the eastern Munisen Ice Shelf as well as the three ice rises Hamarryggen, Lokeryggen and Derwael. Even though the Princess Ragnhild coast has been close to balance in recent decades and is likely dynamically stable , the individual catchments are sensitive to increased ocean melting because some tributary glaciers rest on a retrograde, landward sloping bed . Together, the catchments drain a land ice mass with a eustatic sea-level equivalent of 2 m.The data are available for both data products (qlook: unfocused; standard: SAR focused) as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.